Improving the properties of heat-induced whey protein hydrogels produced under the effects of moderate electric fields - Pereira, Ricardo (2013)
Research on whey utilization is now being largely focused on exploiting their physiochemical and bioactive properties. Whey protein isolate (WPI) is among the most importante whey-derived ingredients and consists of products puriﬁed to a high protein content (>90%). The denaturation and aggregation kinetic behavior of WPI upon heating is of particular relevance; when properly engineered and controlled, it results in the production of novel nano-structures with many potential uses in Food formulations (i.e. enhancement of textural properties, action as stabilizing agents and delivery of biologically active substances. Combination of heat and moderate electric fields (MEF) treatment interferes with unfolding and aggregation pathways of whey biopolymers